Physical environment and life expectancy at birth in Mexico: an eco-epidemiological study - Alvaro J. Idrovo
The objective of this ecological study was to ascertain the effects of physical environment on life expectancy at birth, using data from all 32 Mexican states. 50 environmental indicators with information about demography, housing, poverty, water, soils, biodiversity, forestry resources, and residues were included in exploratory factor analysis. Four factors were extracted: population vulnerability/susceptibility, and biodiversity (FC1), urbanization, industrialization, and environmental sustainability (FC2), ecological resilience (FC3), and free-plague environments (FC4). Using OLS regressions, FC2, FC3, and FC4 were found to be positively associated with life expectancy at birth, while FC1 was negatively associated. This study suggests that physical environment is an important macro-determinant of the health of the Mexican population, and highlights the usefulness of ecological concepts in epidemiological studies.